Synthesis and Characterization of Some New Tropylidene Derivatives and Studying their Biological Activities - Al-Abbasee, Muath Jabbar Tarfa; jebur, Ahmood khalaf; Shihab, Afraa Sabir (Iraqi Journal of Science, 2021)
Some new tropylidene derivatives were prepared in this work and their in vitro antibacterial and antifungal activities were studied. All the prepared compounds were characterized by their physical properties, such as melting point and color, and chemical properties, using the techniques of FT-IR, 1H-NMR and 13C-NMR.